2019
DOI: 10.1016/j.funeco.2019.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric Epichloë species and chemotypic profiles in natural populations of Lolium perenne

Abstract: The distribution of different Epichloë species within eight natural populations of Lolium perenne was studied. In total, 40.2% of the asymptomatic plants were infected by Epichloë festucae var. lolii or by Epichloë typhina. Both species occurred in sympatry at seven populations, and some plants had dual infections by both taxa. No hybrid taxa such as Epichloë hybrida were detected. Epichloë festucae strains were classified into two morphotypes, M1 and M3, according to culture characters, both morphotypes occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Climate change could result in environmental conditions that are more conducive to survival of infected grasses, which may increase their distribution to a level that endophyte-infected plants could dominate grasslands. Previous studies on grasslands in Germany and Spain showed that single individuals of cool season grass species infected with Epichloë can contain alkaloid concentrations above the toxicity thresholds for livestock [35,46,55], which for ergovaline are 300-500 ppb for cattle and horses, and 500-800 ppb for sheep, with lolitrem B concentrations toxic at 1800-2000 ppb [48]. In typical meadows, the infected toxic grasses are diluted by a high diversity of other species and low infection frequencies, so have been of little concern for causing toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change could result in environmental conditions that are more conducive to survival of infected grasses, which may increase their distribution to a level that endophyte-infected plants could dominate grasslands. Previous studies on grasslands in Germany and Spain showed that single individuals of cool season grass species infected with Epichloë can contain alkaloid concentrations above the toxicity thresholds for livestock [35,46,55], which for ergovaline are 300-500 ppb for cattle and horses, and 500-800 ppb for sheep, with lolitrem B concentrations toxic at 1800-2000 ppb [48]. In typical meadows, the infected toxic grasses are diluted by a high diversity of other species and low infection frequencies, so have been of little concern for causing toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Single samples exceeded toxicity thresholds in both studies, but not on population level. We assume that the difference in alkaloid concentrations often dilutes on population level in Germany similar to other regions, e.g., Spain [54].…”
Section: Field Study In Germanymentioning
confidence: 99%
“…The kinds of alkaloids produced in different grass–endophyte symbionts vary with the species of fungal endophytes; for example, Epichloë festucae var. lolii in perennial ryegrass ( Lolium perenne ) can produce peramine, ergovaline and lolitrem B [ 14 , 26 ], Epichloë funkii in Achnatherum robustum produces ergot alkaloids and indole-diterpene alkaloids [ 24 ], and Epichloë inebrians in Achnatherum inebrians only produces ergot alkaloids [ 27 ], while some Epichloë endophytes do not produce alkaloids [ 21 ]. In addition, some studies have found that Epichloë endophytes can produce some antifungal active metabolites when cultured separately in vitro, including gamahonolides A and B, gamahorin, chokols A–G, indole derivatives and epichlicin [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%